Analisis Pengaruh Faktor Lingkungan Dan Faktor Pekerja Terhadap Kapasitas Fungsi Paru Pekerja Industri Meubel Di Kota Pekanbaru Tahun 2013 - Frisca Raynel; Zulkarnaini Zulkarnaini; Yulis Hamidy (Dinamika Lingkungan Indonesia, 2014)
The objectives of this research are to analyze and investigate the influence ofenvironmental factors and characteristics of workers towards lung function capacity offurniture industry workers at Pekanbaru. This study used a cross-sectional design, with totalsampling technique as much as 52 people of furniture industry workers. The result showed,there are 3 variables which affect lung function capacity of workers, that is exposure torespirable dust, smoking habit, and use of self protective tools. From the bivariate analyzes, itfound that exposure to respirable dust is the most dominant variable that affect the capacityof pulmonary function with p value: 0,000, that is equal to 41 times higher than workers withdust levels below the threshold value.